Toxic Capital Everywhere: Mapping the Coordinates of Regulatory Tolerance - Tombs, Steve (Social justice, 2014)
The article examines the political economy of toxic capital, describing the destructive nature of capitalist production. Topics include government regulation of industrial safety, industrial accidents, and the 1984 Union Carbide pesticide plant disaster that occurred in Bhopal, India. Information is provided on industrial health and safety breaches.